Principles and challenges of quality management in primary care - Aljuhani, Faisal Ahmad; Alhejji, Abdullah Mohammed; Aljaloud, Musaad Sulaiman; Al Shammari, Turki Habib; Aljurbua, Abdulelah Abdullah; Turkostany, Nesma Saleh; Alhassan, Abdullah Hasem; Aljuaid, Nada Naji; Jereb, Mashael Mohammed; Alhussain, Sarah Abbas; Hutaylah, Ibrahim Saleh Al (International Journal Of Community Medicine And Public Health, 2022)
The provision of care is fragmented in the complex field of health care. In order to fulfil the needs of all groups in healthcare, quality can serve as a common paradigm. For lowering adverse events, enhancing efficiency, and improving patient satisfaction, the evaluation of quality in medical settings is becoming more and more critical. The objective of the healthcare system is to give a specific patient the best care possible from a certified practitioner in the right environment. Quality management in healthcare is the management of system designs, policies, and procedures that reduce, if not completely eradicate, harm while enhancing patient care and outcomes. Quality improvement must be ongoing in order to improve efficiency, patient safety, the delivery of evidence-based healthcare, and health outcomes. Hospitals were early adopters of quality improvement but adopting evidence-based interventions is still difficult in many primary care settings. The purpose of this research is to review the available information about principles and challenges of quality management in primary care. Relationship management, customer focus, effective leadership, employee engagement, process approach, and improvement are few of the principles of quality management. Various challenges including severely departmentalized, bureaucratic, and hierarchical structure, professional autonomy, conflicts between managers and professionals among several others are faced in primary care. Research in future can effectively contribute to addressing challenges and developing guidelines for overcoming these challenges in primary care to ensure best quality healthcare services.